Disentangling future effects of climate change and forest disturbance on vegetation composition and land surface properties of the boreal forest - Layritz, Lucia S.; Gregor, Konstantin; Krause, Andreas; Kruse, Stefan; Meyer, Benjamin F.; Pugh, Thomas A.M.; Rammig, Anja (Biogeosciences, 2025)
Forest disturbances can cause shifts in boreal vegetation cover from predominantly evergreen to deciduous trees or non-forest dominance. This, in turn, impacts land surface properties and, potentially, regional climate. Accurately considering such shifts in future projections of vegetation dynamics under climate change is crucial but hindered (e.g., uncertainties in future disturbance regimes). In this study, we investigate how sensitive future projections of boreal forest dynamics are to additional changes in disturbance regimes. We use the dynamic vegetation model LPJ-GUESS to investigate and disentangle the impacts of climate change and intensifying disturbance regimes in future projections of boreal vegetation cover as well as changes in land surface properties such as albedo and evapotranspiration. Our simulations find that (1) warming alone drives shifts towards more densely forested landscapes, (2) more intense disturbances reduce tree cover in favor of shrubs and grasses, and (3) the interaction between climate and disturbances leads to an expansion of deciduous trees. Our results additionally indicate that warming decreases albedo and increases evapotranspiration, while more intense disturbances have the opposite effect, potentially offsetting climate impacts. Warming and disturbances are thus comparably important agents of change in boreal forests. Our findings highlight future disturbance regimes as a key source of model uncertainty and underscore the necessity of accounting for disturbances-induced effects on vegetation composition and land surface-atmosphere feedback.
Publisher Copyright: © Author(s) 2025.